PENGARUH BERAT DAN LAMA WAKTU PENYEDUHAN TERHADAP KADAR KAFEIN TEH - Ririn Yuningsih; Samingan Samingan; Muhibbuddin Muhibbuddin (Universitas Syiah Kuala, 2012)
Tea is the most consumed beverage after water and touted as a beverage rich in benefits. In addition to the benefits of tea, there are also substances contained in tea that result in less good for the body, the substance is caffeine. Amount of caffeine depending on the spesies, processing and brewing method. The research